“The nobles”: a phenomenology of teachers teaching special children in Malaysian classrooms / Haniza Sarijari - Sarijari, Haniza (2014)
This study is a phenomenological inquiry which seeks to understand the problems encountered by 8 teachers teaching special children at a school in Batu Pahat . The diversified children from different backgrounds and cultures make these teachers’ job even challenging. This is also the result of language incompetency which interferes the communication in the classroom. Therefore, a qualitative research was chosen to investigate the problems with the help of 8 interview sessions and 8 observations in different classes. Aggressive and passive behaviours were pointed out as the most disruptive conduct experienced by special education teachers. The inability of these children to function with language had caused the problem in managing the class particularly with the hyperactive ones. Knowing special children individually could help the teachers in understanding the reasons for such behaviour patterns. Parents are the most helpful resource to get the necessary information about these special children. Nevertheless, the lack of involvement from parents leads to the incapability to search for the most suitable method to deal with these particular children. Special education teachers as the participants of this study require full support from parents in order to provide effective learning environment that suits the needs of special children.